Anuros do Cerrado em um mundo em mudança: fatores de vulnerabilidade - PACÍFICO, Eduardo dos Santos (2011)
Endemic species have higher risk of extinction and are the focus of conservation efforts because they are confined to specific areas. Evidently, extinction vulnerability variation among endemic species should be mainly explained by their range distribution. Because they have specific eco-physiological traits, anurans are particularly sensitive to global climate change (GCC). Thus, the goals of this study are to present a new anuran endemic species list of Cerrado, to discuss issues related to endemism and to determine if the current potential distribution is able to predict the species extinction vulnerability in GCC. We analyze anuran species that were considered endemic in previous studies plus recently described species. We used two modeling procedures (Maxent and Mahalanobis distance method), three climate models (CCCma, CSIRO and HadCM3) and two carbon emissions scenarios (A2 and B2). Analyses were performed separately for each set of conditions (method, model and scenario) and then we analyzed the emergent pattern. There are 33 Cerrado endemic anuran species, belonging to ten families, representing 20.4% of Cerrado s anurans and 3.8% of Brazilian anurans. Most species have few occurrence points (mean ± standard deviation: 4.9 ± 4.6). Twelve endemic species have all their occurence points near to the boundaries of Cerrado and twelve have all their occurence points in the center of the biome. Small changes in biome boundaries alter the number of endemic species. Therefore, the endemism concept is strongly linked to the biome definition, the sampling effort, the correct species identification and the existing information released. Using the biome limits defined by the Brazilian government, Cerrado endemic anurans with small range distribution have less overlap between the current and the future distributions than Cerrado endemic anurans with large range distribution, indicating that species with small range have a higher risk of extinction. Nevertheless, Cerrado endemic anurans with small range distribution have more proportional gain of suitable area in the future than Cerrado endemic anurans with large range distribution. Consequently, there will be adequate area for all species. However, only species that could move to suitable places will persist. Hence, species persistence, mainly for species with small range size, depends largely on the connectivity of suitable habitat and dispersal rates that allow the colonization of new areas.